2014
DOI: 10.1037/a0037728
|View full text |Cite
|
Sign up to set email alerts
|

Workplace bullying erodes job and personal resources: Between- and within-person perspectives.

Abstract: Workplace bullying is a serious psychosocial occupational hazard. Despite a wealth of empirical study, research has rarely examined the mechanisms through which bullying has its negative effects. Accordingly, using both between- and within-person approaches, we investigated the erosion of job (Study 1) and personal (Study 2) resources following workplace bullying, mediated by the depletion of emotional energy. In Study 1, self-report survey data were collected from 221 retail workers at 2 time-points spaced 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
111
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(117 citation statements)
references
References 79 publications
6
111
0
Order By: Relevance
“…Evidence from dairy studies examining bullying support this dynamic view. For example, in a weekly diary study, Tuckey and Neall (2014) demonstrated that bullying negatively impacted on both optimism and selfefficacy. They also found that exposure to bullying significantly fluctuates within persons over a short period of time.…”
Section: Theoretical Implications and Suggestions For Future Researchmentioning
confidence: 99%
“…Evidence from dairy studies examining bullying support this dynamic view. For example, in a weekly diary study, Tuckey and Neall (2014) demonstrated that bullying negatively impacted on both optimism and selfefficacy. They also found that exposure to bullying significantly fluctuates within persons over a short period of time.…”
Section: Theoretical Implications and Suggestions For Future Researchmentioning
confidence: 99%
“…Leymann25 has posited several consequences of bullying that match those thought to be a precursor of suicide in the IPTS model, including social isolation, desperation, hopelessness and despair; however, there appears to be little empirical research confirming these associations. Other research has linked workplace bullying with reduced self-esteem and increases in emotional exhaustion,26 27 suggesting that a ‘resource loss spiral’ might also be a useful framework for conceptualising how workplace bullying translates into suicidal ideation and behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…weekly or daily) exposure. It is established that workplace bullying adversely impacts employees in several ways (see Nielsen and Einarsen 2012;Nielsen et al 2014 for reviews), including outcomes such as physical and mental health problems Hansen et al 2011;Høgh et al 2011bHøgh et al , 2012bKivimӓki et al 2003;Tuckey and Neall 2014), low job-related well-being (Bowling and Beehr 2006;Djurkovic et al 2008;Rodríguez-Muñoz et al 2009), job turnover (Clausen et al 2013;Høgh et al 2011a), professional dropout (Høgh et al 2012a) and sickness absence (Clausen et al 2012;Kivimäki et al 2000;Ortega et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…This implies that individuals, when confronted with resource-depleting circumstances, will tend to adopt behaviours that are primarily directed at protecting their residual resources and/or at preventing further resource loss. Among stressful working conditions, being subjected to workplace bullying is known for the potential it has to bring about a substantial loss of both personal and job-related resources (Tuckey and Neall 2014). In the context of bullying, engaging in SP can be seen as a possible behavioural strategy that targets adopt to counter such process of resource depletion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation